The Rwa Bhineda Painting Principles: The Art of I Dewa Nyoman Batuan - I Made Ruta; I Made Saryana; Gede Yoga Kharisma Pradana; Ni Wayan Masyuni Sujayanthi; Ni Made Purnami Utami (RIRAI Publisher, 2023)
Rwa Bhineda are two distinct characteristics that exist in this life. The goal of this article is to reveal the principle of rwa bhineda in I Dewa Nyoman Batuan's mandala paintings. The mandala paintings by I Nyoman Batuan are very distinctive and have inspired many other artists' paintings. However, there has been no study that discusses the principle of rwa bhineda, which makes mandala paintings by I Dewa Nyoman Batuan look distinctive. This article discusses the principle of rwa bhineda in a painting by I Dewa Nyoman Batuan and the meaning of rwa bhineda in a mandala painting by I Dewa Nyoman Batuan. This study uses a qualitative method. The data sources for this study were mandala paintings by I Dewa Nyoman Batuan himself, mandala painters, cultural observers, and people observing mandala paintings selected based on purposive sampling and snowball techniques. All data obtained through observation, interviews, and literature studies were analyzed qualitatively and interpretatively using aesthetic theory and deconstruction theory. The results of the research show that the principle of rwa bhineda in the mandala painting by I Dewa Nyoman Batuan is made in the form of a circle, which is beautified by the duality motif. The principle of rwa bhineda in mandala paintings by I Dewa Nyoman Batuan has an aesthetic meaning, a cultural meaning, and a counter-destruction meaning.